Advances in Amino Acid-Based Chemistry - Rosanna Palumbo; Hayarpi Simonyan; Giovanni N. Roviello (MDPI AG, 2023)
Numerous applications of amino acid-based compounds and peptide derivatives in different biomedicine- and nanotechnology-related fields were described in the recent scientific literature [...]